Feminist Scholarship and Family Sociology: New Ways of Thinking, Outstanding Questions - Luxton, Meg (Canadian Review of Sociology, 2015)
The article discusses the research and scholarship of feminist scholars on family sociology in Canada from the 1960s through the mid 2010s, including the feminist sociology of families. The relationship between neoliberalism and gender, including the alleged indifference of neoliberal government policies to gender of income earners, is discussed. An overview of Canada's national statistics agency Statistics Canada's data on labor, including on domestic labor, gender divisions in labor, women's employment and unpaid household work, is provided.
Keywords: FAMILIES – Canada; FEMINIST theory – History; FEMINISTS – History; GENDER – Social aspects; HOUSEKEEPING – Social aspects; LABOR – Canada; LEARNING & scholarship – History; NEOLIBERALISM – Social aspects; SOCIOLOGICAL research – Canada; SOCIOLOGY – Canada; STATISTICS Canada; WOMEN – California – Employment